High-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization as well as preparation method and application of high-performance polylactic acid / poly (4-hydroxybutyrate) composite material

Through the use of free radical polymer (methyl acrylic acid hydroglceride) as a container in PLA/P4HB composite materials, it improves the compatibility of the material and solves the problem of low interface adhesion and separation. Improve the mechanical properties and shape memory properties of materials.

CN119371791AActive Publication Date: 2025-01-28QINGDAO UNIV OF SCI & TECH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411716449.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-01-28
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

Due to the large structural differences between the two materials, the existing PLA/P4HB composite materials lead to low interfacial adhesion and phase separation, which reduces the strength and toughening effect of the material, and has lower performance than expected.

Method used

The free radical aggregation method is used to synthesize the polymer (PGMA) (PGMA) with different molecular weights (PGMA) as a reactive reaction agent to improve the compatibility between PLA and P4HB through interface reactions.

Benefits of technology

Improve the stretching strength, fracture and extension and shape memory performance of polystrackic acid/polystium (4-hydroxyl-pyloric acid) composite materials, and meet the needs of packaging and smart devices with high tough performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371791A_ABST
    Figure CN119371791A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization as well as a preparation method and application thereof, and belongs to the technical field of preparation of high-performance biodegradable high polymer materials. The material is prepared from the following raw materials in parts by weight: 60 to 80 parts of polylactic acid, 10 to 40 parts of poly (4-hydroxybutyrate), 0.5 to 8 parts of polyglycidyl methacrylate and 0.1 to 0.5 part of antioxidant. According to the present invention, the compatibility between the polylactic acid and the poly (4-hydroxybutyrate) is improved by the glycidyl polymethacrylate through the chemical reaction at the interface, the glycidyl polymethacrylate can be well dispersed in the matrix, the interfacial tension of the composite material is reduced, and the adhesion between the polylactic acid and the poly (4-hydroxybutyrate) can be improved; further, the tensile strength, the elongation at break and the shape memory performance of the polylactic acid / poly (4-hydroxybutyrate) composite material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of high-performance biodegradable polymer materials, and specifically relates to a high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization, and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] With the maturity of global plastic production technology, the annual output of plastics has reached 450 million tons in recent years, generating more than 340 million tons of plastic waste, which has put tremendous pressure on the environment. It is estimated that by 2050, there will be 26 billion metric tons of plastic waste waiting to be processed, half of which will be discarded in the environment, bringing long-term waste management problems. This has made polymer materials with renewable and degradable properties a research hotspot in the past two decades. Among all biodegradable polymers, polylactic acid (PLA) shows great market potential due to its good biocompatibility and processing performance, complete renewability and relatively low production cost, but its application is affected by brittleness. In order to compensate for the brittleness of polylactic acid, flexible poly (4-hydroxybutyrate) (P4HB) is usually introduced. P4HB is also a degradable biomaterial and has excellent toughness and impact strength. PLA / P4HB composites are very promising materials because PLA has good physical and mechanical properties and P4HB has good toughness, and the properties of these two materials can complement each other. However, the mixture of PLA and P4HB can only show perfect performance when they are compatible in the product. The experiment found that due to the large structural differences between the two materials, the low interfacial adhesion and macroscopic phase separation between the two polyesters will lead to immiscibility. More than 10% of P4HB in PLA resin will undergo phase separation, greatly reducing the strength of the blended material and the toughening effect, resulting in the performance of the blended material being lower than expected. Therefore, it is necessary to explore an effective compatibilizer to improve the interaction between PLA and P4HB.

[0004] So far, the common method for increasing the compatibilization of PLA / P4HB composites is to add reactive compatibilizers, such as chain extenders such as epoxy, anhydride, isocyanate, or a third component with high reaction activity. The principle is to form different copolymers in situ during the blending process to increase the compatibilization. For example, patent CN105504727A discloses a high-toughness fully degradable polylactic acid-based composite material, which uses substituted dibenzylidene sorbitol and polyhydroxybutyrate grafted methacrylate glycidyl as reactive compatibilizers to modify polylactic acid / poly 3-hydroxybutyrate-co-4-hydroxybutyrate to enhance interfacial adhesion, and blends the compatibilizer with the composite material by melt blending extrusion to prepare a fully degradable high-toughness fully degradable polylactic acid-based composite material, but the toughening effect of the reactive compatibilizer is limited, and the mechanical properties of the material still need to be further improved. Summary of the invention

[0005] In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization, and a preparation method and application thereof. The present invention adopts a simple free radical polymerization method to synthesize poly (glycidyl methacrylate) (PGMA) of different molecular weights, and uses it as a reactive compatibilizer for the PLA / P4HB system. The prepared polylactic acid / poly (4-hydroxybutyrate) composite material has high tensile strength, elongation at break and shape memory performance, can be widely used in the fields of packaging and smart devices requiring high strength and toughness, and has significant economic value and social benefits.

[0006] In order to achieve the above object, the technical solution of the present invention is:

[0007] The first aspect of the present invention provides a high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization, which is prepared from the following raw materials:

[0008] 60-80 parts of polylactic acid, 10-40 parts of poly(4-hydroxybutyrate), 0.5-8 parts of polyglycidyl methacrylate, and 0.1-0.5 parts of antioxidant.

[0009] In some embodiments of the present invention, the molecular weight of the polylactic acid is 15-25 kDa.

[0010] In some embodiments of the present invention, the molecular weight of the poly (4-hydroxybutyrate) is 10-15 kDa.

[0011] In some embodiments of the present invention, the molecular weight of the poly(glycidyl methacrylate) is 4-10 kDa.

[0012] In some embodiments of the present invention, the antioxidant is any one or more of antioxidant 1010 and antioxidant 245.

[0013] In some embodiments of the present invention, the high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization is prepared from the following raw materials:

[0014] 65-75 parts of polylactic acid, 15-35 parts of poly(4-hydroxybutyrate), 1-8 parts of polyglycidyl methacrylate, and 0.1-0.4 parts of antioxidant.

[0015] In some embodiments of the present invention, the high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization is prepared from the following raw materials:

[0016] 70 parts of polylactic acid, 30 parts of poly(4-hydroxybutyrate), 1-8 parts of polyglycidyl methacrylate, and 0.1-0.4 parts of antioxidant.

[0017] In some embodiments of the present invention, the high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization has a tensile strength of 43.8 to 55.3 MPa, an elongation at break of 68.8% to 265.1%, a shape fixation rate of 97.1% to 97.8%, and a shape recovery rate of 78.7% to 93.6%.

[0018] The second aspect of the present invention provides a method for preparing the above-mentioned high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization, comprising:

[0019] melt-blending polylactic acid, poly(4-hydroxybutyrate) and an antioxidant;

[0020] adding poly(glycidyl methacrylate) and continuing to blend and extrude and granulate to obtain granules;

[0021] After the pellets are molded, a high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization is obtained.

[0022] In some embodiments of the present invention, the blending temperature is 165-210°C, preferably 165-200°C.

[0023] In some embodiments of the present invention, the forming is compression molding or injection molding;

[0024] Preferably, the molding temperature is 165-200° C., and the molding pressure is 10-80 MPa.

[0025] In some embodiments of the present invention, the preparation method of polyglycidyl methacrylate comprises:

[0026] purifying the glycidyl methacrylate monomer to obtain a purified monomer;

[0027] Dissolve copper bromide and tris(2-pyridylmethyl)amine in an organic solvent, and stir until dissolved to obtain a catalyst solution;

[0028] The purified glycidyl methacrylate monomer is mixed with a solvent and a catalyst solution, an initiator is added, and heating is performed to initiate a polymerization reaction to obtain polyglycidyl methacrylate.

[0029] In some embodiments of the present invention, the purification comprises the following steps:

[0030] The glycidyl methacrylate monomer is sequentially passed through neutral alumina and absorbent cotton to obtain a purified monomer.

[0031] Preferably, the amount of the neutral alumina is 4-5 mL.

[0032] Preferably, the organic solvent is any one of N-dimethylformamide, dimethyl sulfoxide and N-methylpyrrolidone.

[0033] Preferably, the solvent is any one of anisole, toluene and chloroform.

[0034] Preferably, the initiator is any one of diethyl 2-bromo-2-methylmalonate, 1-bromoethylbenzene, 1,2-dibromoethane, ethyl 2-bromopropionate and 1,3-dibromopropane.

[0035] Preferably, after the polymerization reaction is completed, the crude product is diluted, stirred, washed, settled and dried to obtain poly(glycidyl methacrylate); further preferably, the crude product is poured into acetone for dilution; further preferably, the drying temperature is 35-45°C.

[0036] The present invention adopts poly(glycidyl methacrylate) obtained by atom transfer radical polymerization as a compatibilizer to enhance the compatibility between polylactic acid and poly(4-hydroxybutyrate), thereby improving the tensile strength, elongation at break and shape memory performance of the composite material.

[0037] The present invention adopts poly(4-hydroxybutyrate) and polylactic acid to blend to solve the problem of high brittleness of polylactic acid, and adopts poly(glycidyl methacrylate) to increase the compatibility of the polylactic acid / poly(4-hydroxybutyrate) blend to promote the compatibility of the two, thereby improving the mechanical properties and shape memory properties of the composite material.

[0038] Specifically, blending polylactic acid with poly(4-hydroxybutyrate) can form a more uniform phase distribution, improve the interfacial interaction between polylactic acid and poly(4-hydroxybutyrate), thereby improving the toughness of polylactic acid and the overall performance of the composite material. After adding poly(glycidyl methacrylate) to the polylactic acid / poly(4-hydroxybutyrate) blend, ring opening and cross-linking reactions will occur to form a small amount of three-dimensional network structure. These cross-linked structures limit the free movement of polymer chains, making the polymer more capable of maintaining its new shape under external stress, and promoting the shape memory properties of the material. In addition, the enhanced degree of entanglement of the molecular chains enables the material to disperse and absorb externally applied stress, providing additional mechanical strength and stability, thereby improving toughness and reducing brittle fracture.

[0039] The third aspect of the present invention provides an application of the above-mentioned high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction volume expansion or the high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction volume expansion prepared by the above-mentioned preparation method in packaging materials, cushioning materials and thermal insulation materials.

[0040] The beneficial effects of the present invention are:

[0041] The present invention uses poly(4-hydroxybutyrate) and polylactic acid to blend to improve the problem of polylactic acid brittleness, and uses poly(glycidyl methacrylate) to increase the volume of the polylactic acid / poly(4-hydroxybutyrate) blend to promote the compatibility of the two, thereby improving the mechanical properties and shape memory properties of the composite material. The polylactic acid / poly(4-hydroxybutyrate) composite material prepared by the present invention has high tensile strength, elongation at break and shape memory properties, with a tensile strength of 43.8 to 55.3 MPa, an elongation at break of 68.8% to 265.1%, a shape fixation rate of 97.1% to 97.8%, and a shape recovery rate of 78.7% to 93.6%. It can be used in the fields of packaging and intelligent devices that require high strength and toughness, and has significant economic value and social benefits.

[0042] Atom transfer radical polymerization is a new controllable polymerization method that can accurately synthesize polymers with predetermined molecular weight, structure and functionality, and has tolerance to functional groups in monomer molecules. Therefore, the molecular weight of the poly(glycidyl methacrylate) used in the present invention is controllable and the molecular weight distribution is narrow. Polylactic acid has a wide range of sources, relatively low production costs, little environmental pollution, good biocompatibility and processing performance, and a wide range of applications. The poly(glycidyl methacrylate) prepared by atom transfer radical polymerization in the present invention can improve the compatibility between polylactic acid and poly(4-hydroxybutyrate) by chemical reaction at the interface, can be well dispersed in the matrix, reduce the interfacial tension of the composite material, can improve the adhesion between polylactic acid and poly(4-hydroxybutyrate), and then improve the tensile strength, elongation at break and shape memory properties of the polylactic acid / poly(4-hydroxybutyrate) composite material.

[0043] The polylactic acid and poly (4-hydroxybutyrate) used in the present invention are both green and environmentally friendly materials such as biodegradable polymer materials or inorganic powder materials. Therefore, the heat-resistant polylactic acid composite material prepared in the present invention is an environmentally friendly and completely biodegradable polymer material, which conforms to the concept of environmental protection and meets the requirements of sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0045] Figure 1 This is the infrared spectrum of polyglycidyl methacrylate prepared in Example 1 of the present invention;

[0046] Figure 2 This is a scanning electron microscope image of the polylactic acid / poly (4-hydroxybutyrate) blend prepared in Comparative Example 2 of the present invention;

[0047] Figure 3 These are scanning electron microscope images of high-performance polylactic acid / poly (4-hydroxybutyrate) composite materials prepared in Examples 2-5 of the present invention; wherein, a is a scanning electron microscope image of the brittle cross-section of the composite material prepared in Example 2, b is a scanning electron microscope image of the brittle cross-section of the composite material prepared in Example 3, c is a scanning electron microscope image of the brittle cross-section of the composite material prepared in Example 4, and d is a scanning electron microscope image of the brittle cross-section of the composite material prepared in Example 5. DETAILED DESCRIPTION

[0048] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0049] Example 1

[0050] A method for preparing polyglycidyl methacrylate comprises the following steps:

[0051] 1) Pour 12 g of glycidyl methacrylate monomer from the top of a syringe filled with 4 mL of neutral alumina and the outlet of which is plugged with cotton wool into a purification system (i.e., a syringe). The glycidyl methacrylate monomer passes through the neutral alumina and the cotton wool in sequence, and then flows out from the outlet of the syringe. The outflowing monomer is the purified monomer and is collected for later use.

[0052] 2) Dissolve 0.0026 g of copper bromide and 0.0035 g of tris(2-pyridylmethyl)amine in 4 mL of NN dimethylformamide and stir until all components are dissolved to form a light green solution to prepare a catalyst solution for later use.

[0053] 3) 12 g of purified glycidyl methacrylate monomer was mixed with 10 mL of anisole and 4 mL of 6.0×10 -3 mol / mL catalyst solution was added to the reactor and stirred to obtain a yellow solution. Then 87 μL of atom transfer radical polymerization initiator 2-

[0054] Diethyl bromo-2-methylmalonate, polymerization was initiated by heating (65°C).

[0055] 4) The crude product obtained after polymerization is poured into a solvent for dilution, and the final product of 7 kDa poly(glycidyl methacrylate) is obtained by stirring, washing, chemical precipitation and drying.

[0056] The prepared poly(glycidyl methacrylate) was subjected to infrared spectrum test. The determination method was as follows: the obtained poly(glycidyl methacrylate) was made into a 0.5 mm thick film and placed on a sample table. The infrared spectrum was measured using a JASCO FI / IR-4700 Fourier transform infrared spectrometer (FTIR). The test mode was reflection mode and the wave number range was 3500 cm -1 ~600cm -1 , resolution 4cm -1 .

[0057] The results are as follows Figure 1 Shown: GMA at 1638cm -1 and 910cm -1 There are strong characteristic peaks at 1638cm -1 The characteristic peak at 910cm -1 The characteristic peak intensity at remains almost unchanged, indicating the successful synthesis of PGMA.

[0058] Example 2

[0059] A high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization is formed by the following formula: PLA: P4HB: PGMA: antioxidant

[0060] 1010=70:30:1:0.3.

[0061] The specific preparation method comprises the following steps:

[0062] Step 1: Add the dried polylactic acid, poly(4-hydroxybutyrate) and antioxidant 1010 through the main feed port of the twin-screw extruder, and then add poly(glycidyl methacrylate) through the side feed port of the twin-screw extruder, melt-blend and extrude, and pelletize to obtain polylactic acid / poly(4-hydroxybutyrate) blended particles. The operating temperature of the twin-screw extruder is 160-210°C.

[0063] Step 2: Under the conditions of a pressure molding machine temperature of 165°C and a pressure of 10 MPa, the polylactic acid / poly (4-hydroxybutyrate) blended particles are pre-pressed for 5 minutes by a pressure molding machine, and finally cold-pressed for 2-5 minutes at a pressure of 10 MPa by means of a water-cooled press plate to obtain a polylactic acid / poly (4-hydroxybutyrate) composite material.

[0064] Example 3

[0065] A high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization is formed by the following formula: PLA: P4HB: PGMA: antioxidant

[0066] 1010=70:30:3:0.3.

[0067] The preparation method of this embodiment is the same as that of embodiment 2.

[0068] Example 4

[0069] A high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization is formed by the following formula: PLA: P4HB: PGMA: antioxidant

[0070] 1010=70:30:5:0.3.

[0071] The preparation method of this embodiment is the same as that of embodiment 2.

[0072] Example 5

[0073] A high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization is formed by the following formula: PLA: P4HB: PGMA: antioxidant

[0074] 1010=70:30:7:0.3.

[0075] The preparation method of this embodiment is the same as that of embodiment 2.

[0076] Comparative Example 1

[0077] A polylactic acid composite material is composed of the following formula: PLA:P4HB:antioxidant 1010=100:0:0.2.

[0078] The specific preparation method is different from that of Example 2 in that: Step 1, adding the dried polylactic acid and antioxidant 1010 through the main feeding port of the twin-screw extruder, melt blending and extruding, and pelletizing to obtain polylactic acid blended particles. The remaining steps are the same as those of Example 2.

[0079] Comparative Example 2

[0080] A polylactic acid / poly (4-hydroxybutyrate) composite material is composed of the following formula: PLA: P4HB: antioxidant 1010 = 70:30:0.2.

[0081] The specific preparation method is different from that of Example 2 in that: Step 1, adding the dried polylactic acid, poly(4-hydroxybutyrate) and antioxidant 1010 through the main feeding port of the twin-screw extruder, melt blending and extruding, and pelletizing to obtain polylactic acid / poly(4-hydroxybutyrate) blended particles. The remaining steps are consistent with those of Example 2.

[0082] The sample obtained in Comparative Example 2 was subjected to a scanning electron microscope (SEM) image analysis of the low temperature brittle fracture, and the results are as follows: Figure 2 As shown: the microstructure of the sample in comparative example 2 presents a typical sea-island structure, P4HB is dispersed as a dispersed phase in the continuous phase PLA, and there is a clear phase interface between the two phases, indicating that the compatibility between PLA and P4HB is poor.

[0083] The samples obtained in Example 2-5 were subjected to low temperature brittle fracture scanning electron microscope (SEM) image analysis, and the results are as follows: Figure 3 As shown: Example 2-5 ( Figure 3 a- Figure 3 As the amount of poly(glycidyl methacrylate) increases, the phase interface becomes blurred, the average particle size of the dispersed phase decreases, and the distribution of the dispersed phase becomes more uniform. Figure 3 c and Figure 3 d) The phase morphology of the sample gradually changes into a co-continuous phase, indicating that the modification effect of adding poly(glycidyl methacrylate) is better, the interfacial tension of polylactic acid and poly(4-hydroxybutyrate) is reduced, the adhesion is enhanced, the compatibility is enhanced, and the interaction force between the two phases is enhanced.

[0084] The samples obtained from Examples 2-5 and Comparative Examples 1-2 were tested for tensile properties and shape memory properties.

[0085] The tensile properties test method uses a GF-HV2000A-C6W computer servo universal testing machine to test the tensile strength and elongation at break of standard type II specimens according to the international GB / T1040.1-2018 standard.

[0086] The tensile data are shown in Table 1. The elongation at break of the sample of Comparative Example 1 is very low. After adding poly (4-hydroxybutyrate), the elongation at break of the sample of Comparative Example 2 is slightly improved, but the degree of improvement is small. In contrast, the samples in Examples 2-5 have both good tensile strength and elongation at break.

[0087] The shape memory of the samples was tested by using a DMA instrument, by applying a cyclically varying stress and measuring the response of the material.

[0088] The specific results of the shape fixation rate and shape recovery rate of the samples are shown in Table 1. The sample of Comparative Example 1 exhibits poor shape memory performance, the shape memory performance of the sample of Comparative Example 2 increases after adding poly(4-hydroxybutyrate), and the shape memory performance of the samples in Examples 2-5 gradually improves with the increase of poly(glycidyl methacrylate).

[0089] Table 1 Performance test results of composite materials obtained in Examples and Comparative Examples

[0090]

[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization, characterized in that: Prepared from the following raw materials: 60-80 parts of polylactic acid, 10-40 parts of poly(4-hydroxybutyrate), 0.5-8 parts of polyglycidyl methacrylate, and 0.1-0.5 parts of antioxidant.

2. The high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization according to claim 1, characterized in that: The molecular weight of the polylactic acid is 15-25 kDa; Preferably, the molecular weight of the poly(4-hydroxybutyrate) is 10-15 kDa; Preferably, the molecular weight of the polyglycidyl methacrylate is 4-10 kDa; Preferably, the antioxidant is any one or more of antioxidant 1010 and antioxidant 245.

3. The high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization according to claim 1 or 2, characterized in that: The high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization is prepared from the following raw materials: 65-75 parts of polylactic acid, 15-35 parts of poly(4-hydroxybutyrate), 1-8 parts of polyglycidyl methacrylate, and 0.1-0.4 parts of antioxidant; Preferably, the high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization is prepared from the following raw materials: 70 parts of polylactic acid, 30 parts of poly(4-hydroxybutyrate), 1-8 parts of polyglycidyl methacrylate, and 0.1-0.4 parts of antioxidant.

4. The high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization according to claim 1 or 2, characterized in that: The high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization has a tensile strength of 43.8 to 55.3 MPa, an elongation at break of 68.8% to 265.1%, a shape fixation rate of 97.1% to 97.8%, and a shape recovery rate of 78.7% to 93.6%.

5. A method for preparing a high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization according to any one of claims 1 to 4, characterized in that: include: melt-blending polylactic acid, poly(4-hydroxybutyrate) and an antioxidant; adding poly(glycidyl methacrylate) and continuing to blend and extrude and granulate to obtain granules; After the pellets are molded, a high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization is obtained.

6. The preparation method according to claim 5, characterized in that: The blending temperature is 165-210°C, preferably 165-200°C.

7. The preparation method according to claim 5, characterized in that: The molding is compression molding or injection molding; Preferably, the molding temperature is 165-200° C., and the molding pressure is 10-80 MPa.

8. The preparation method according to claim 5, characterized in that: The preparation method of the polyglycidyl methacrylate comprises: purifying the glycidyl methacrylate monomer to obtain a purified monomer; Dissolve copper bromide and tris(2-pyridylmethyl)amine in an organic solvent, and stir until dissolved to obtain a catalyst solution; The purified glycidyl methacrylate monomer is mixed with a solvent and a catalyst solution, an initiator is added, and heating is performed to initiate a polymerization reaction to obtain polyglycidyl methacrylate.

9. The preparation method according to claim 8, characterized in that: The purification comprises the following steps: The glycidyl methacrylate monomer is sequentially passed through neutral alumina and absorbent cotton to obtain a purified monomer; Preferably, the amount of the neutral alumina is 4-5 mL; Preferably, the organic solvent is any one of N-dimethylformamide, dimethyl sulfoxide and N-methylpyrrolidone; Preferably, the solvent is any one of anisole, toluene and chloroform; Preferably, the initiator is any one of diethyl 2-bromo-2-methylmalonate, 1-bromoethylbenzene, 1,2-dibromoethane, ethyl 2-bromopropionate and 1,3-dibromopropane; Preferably, after the polymerization reaction is completed, the crude product is diluted, stirred, washed, settled and dried to obtain poly(glycidyl methacrylate); further preferably, the crude product is poured into acetone for dilution; further preferably, the drying temperature is 35-45°C.

10. Use of a high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization as described in any one of claims 1 to 6 or a high-performance polylactic acid / poly (4-hydroxybutyrate) composite material based on interfacial reaction compatibilization prepared by the preparation method described in any one of claims 7 to 9 in packaging materials, cushioning materials and thermal insulation materials.

Citation Information

Patent Citations

  • High-tenacity full-degradable polylactic acid based composite and preparation method thereof

    CN105504727A

  • Polylactic acid / chemically modified natural rubber blend material and preparing method thereof

    CN106366596A

  • Poly-3-hydroxybutyrate composite material and preparation method thereof

    CN108219407A

  • Poly (4-hydroxybutyrate) / polylactic acid blend fiber and preparation method thereof

    CN114318588A

  • Biodegradable graft copolymer material for polylactic acid and preparation method thereof

    CN116285259A